Performance evaluation of corner effect in 3G network in user perspective / Muhammad Ashraf Zulkapli - Zulkapli, Muhammad Ashraf (2013)
The purpose of this project is to analyze corner effect in 3G network. In this paper, two 3G service provider in Malaysia were selected in order to obtain more accurate data. Software used in this drive test is RF signal tracker and G-Net track from Google Play installed on android mobile phone. The drive test data was collected alongside Jalan Tun Razak, Jalan Ampang and Jalan Yap Kwan Seng. The drive test data further analyze by using Google Earth, and graph was plot by using Microsoft Excel .The main parameter to determine corner effects are Ec/No and RSCP level of User Equipment. From drive test conducted, Celcom show a better performance in 3G signal quality as compare to U Mobile. Corner effect was happen near to Ampang Park and both service providers experienced the same problem. Corner effect happen when user equipment experience sudden drop in signal level. Problem occur because of blockage in line of sight between user equipment and Node B. Detail analysis on corner effect included in next part of this paper.